Validation of the Serbian Adaptation of the Self-Absorption Scale - Kostić, Senka M.; Stanojević, Dragana (Primenjena psihologija, 2022)
McKenzie and Hoyle made the first Self-Absorption Scale. Since this scale is not available in Serbian, we designed two studies aimed at its adaptation (Study 1, N = 400), and validation of the instrument (Study 2, N = 212). Results of Study 1 confirmed original two-factorial structure, but without two items on each subscale. The reliability of the public self-absorption was α = 0.75; and α = 0.72 for the private self-absorption. The factors in both, the original and adapted version, are congruent (measured by Tucker`s congruence coefficient). Results of Study 2 showed that self-absorption was positively correlated to the most aspects of pathological narcissism, self-consciousness, depression, stress and anxiety. Also, it was negatively correlated to self-esteem. We can conclude that the Self-Absorption Scale is short, reliable, and valid measure for assessing the pathological aspect of self-focusing on Serbian population.